Peran Perawat Dalam Menangani Pasien Dengan Penyakit Menular Seksual Di Klinik Kesehatan Reproduksi - Abbad Nailun; Justin Gilbert (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2023)
Data management in dental clinics is an important component in realizing a data processing system in dental clinics. Manual data management has many weaknesses, apart from taking a long time, its accuracy is also less acceptable, because the possibility of errors is very large. With the support of current data processing system technology, manual data processing work can be replaced with a data processing system using a computer. Apart from being faster and easier, data management also becomes more accurate. When processed, accurate data will produce accurate data. Accurate data is very useful for making decisions, both for management and others.